Monitoring on a shoestring: Low cost solutions for digital manufacturing. (2021) - Hawkridge, Gregory; Mukherjee, Anandarup; McFarlane, Duncan; Tlegenov, Yedige; Parlikad, Ajith K.; Reyner, Nicholas J.; Thorne, Alan
Abstract: Digital transformation can provide a competitive edge for many manufacturers, however many smaller companies may not have the capabilities needed to embrace this opportunity and may be left behind. This paper reports on an approach which is attempting to alleviate this by creating a low-cost pathway to help manufacturing small and medium sized enterprises (SMEs) engage with digitalisation. This paper focuses on industrial monitoring and explores the potential for developing simple monitoring systems that solve real operation challenges in SMEs using low-cost, off-the-shelf technologies. A blueprint for developing such systems is presented and then exemplified through a case study system. The paper concludes that low-cost monitoring can be feasible given the right application and operating environment.